Pertanggungjawaban Pidana Pelaku Tindak Pidana Pelecehan Seksual oleh Anggota TNI terhadap Anak - Deisya Devita Mayshanda; Dini Dewi Heniarti (UPT Publikasi Ilmiah Unisba, 2023)
ABSTRACT- Error or criminal responsibility is a requirement for criminalization or imposition of criminal sanctions on perpetrators of criminal acts, in addition to criminal acts as the first requirement for criminalization. The judge’s consideration plays an important role in determining the value of the judge’s decision, especially in terms of justice and legal certainty. This study aims to determine the criminal responsibility of perpetrators of sexual harassment by members of the Indonesian National Army reviewed from Law No. 35 of 2014 and the judge’s consideration in the case of sexual harassment by members of the Indonesian National Army Decision Number 35-K/PM.I-07/AD/VI/2022 is in accordance with the purpose of criminalization. This research uses a descriptive qualitative approach. The type of research is normative juridical, the research specification is descriptive-analytical, and uses library research data collection techniques. The criminal responsibility of perpetrators of sexual harassment by members of the Indonesian National Army with Decision Number 35-K/PM.I-07/AD/VI/2022, is in accordance with the provisions of Article 81 paragraph (2). However, regarding the Judge’s Consideration in the case of sexual harassment by members of the Indonesian National Army Decision Number 35-K/PM.I-07/AD/VI/2022 has not yet been in accordance with the purpose of criminalization, where the Panel of Judges imposed sanctions below the minimum which will not give a deterrent effect that can prevent sexual harassment of children. ABSTRAK-Kesalahan atau pertanggungjawaban pidana merupakan syarat pemidanaan atau pengenaan pidana kepada pelaku tindak pidana, di samping tindak pidana sebagai syarat pemidanaan yang pertama. Pertimbangan hakim sangat penting dalam menentukan nilai putusan hakim, terutama dalam hal keadilan dan kepastian hukum. Penelitian ini bertujuan untuk mengetahui pertanggungjawaban pidana pelaku tindak pidana pelecehan seksual oleh Anggota Tentara Nasional Indonesia ditinjau dari UU No. 35 Tahun 2014 dan pertimbangan hakim dalam kasus tindak pidana pelecehan seksual oleh Anggota Tentara Nasional Indonesia Putusan Nomor 35-K/PM.I-07/AD/VI/2022 sudah sesuai dengan tujuan pemidanaan. Penelitian ini menggunakan pendekatan dengan metode kualitatif yang sifatnya deskriptif. Jenis penelitiannya Yuridis Normatif, spesifikasi penelitian bersifat Deskriptif-Analitis, dan menggunakan teknik pengumpulan data kepustakaan (Library Research). Pertanggungjawaban pidana pelaku tindak pidana pelecehan seksual oleh Anggota Tentara Nasional Indonesia dengan Putusan Nomor 35-K/PM.I-07/AD/VI/2022, sesuai dengan ketentuan Pasal 81 ayat (2). Akan tetapi terkait dengan Pertimbangan Hakim dalam kasus tindak pidana pelecehan seksual oleh Anggota Tentara Nasional Indonesia Putusan Nomor 35-K/PM.I-07/AD/VI/2022 belum sesuai dengan tujuan pemidanaan, di mana Majelis Hakim menjatuhkan sanksi dibawah minimal yang merupakan tidak akan memberi efek jera yang dapat mencegah terjadinya pelecehan seksual pada anak.